PDGFRα depletion attenuates glioblastoma stem cells features by modulation of STAT3, RB1 and multiple oncogenic signals - Cenciarelli, Carlo (Oncotarget, 2016)
Platelet derived growth factor receptors (PDGFRs) play an important role in tumor pathogenesis, and they are frequently overexpressed in glioblastoma (GBM). Earlier we have shown a higher protein expression of PDGFR isoforms (α and β) in peritumoral-tissue derived cancer stem cells (p-CSC) than in tumor core (c-CSC) of several GBM affected patients. In the current study, in order to assess the activity of PDGFRα/PDGF-AA signaling axis, we performed time course experiments to monitor the effects of exogenous PDGF-AA on the expression of downstream target genes in c-CSC vs p-CSC. Interestingly, in p-CSC we detected the upregulation of Y705-phosphorylated Stat3, concurrent with a decrement of Rb1 protein in its active state, within minutes of PDGF-AA addition. This finding prompted us to elucidate the role of PDGFRα in self-renewal, invasion and differentiation in p-CSC by using short hairpin RNA depletion of PDGFRα expression. Notably, in PDGFRα-depleted cells, protein analysis revealed attenuation of stemness-related and glial markers expression, alongside early activation of the neuronal marker MAP2a/b that correlated with the induction of tumor suppressor Rb1. The in vitro reduction of the invasive capacity of PDGFRα-depleted CSC as compared to parental cells correlated with the downmodulation of markers of epithelial-mesenchymal transition phenotype and angiogenesis. Surprisingly, we observed the induction of anti-apoptotic proteins and compensatory oncogenic signals such as EDN1, EDNRB, PRKCB1, PDGF-C and PDGF-D. To conclude, we hypothesize that the newly discovered PDGFRα/Stat3/Rb1 regulatory axis might represent a potential therapeutic target for GBM treatment.